SWOT Analysis as an Organizational Development Strategy for Morowali Regency - Rivai, Abdul; Rahmayanti Rivai, Dian (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research aims to analyze SWOT as a strategy for organizational development in Morowali Regency. This research uses a combined approach between qualitative methods to gain a comprehensive understanding of the SWOT factors that influence organizations. Purposive sampling technique was used to determine informants, involving government officials, organizational members, stakeholders and related experts who have in-depth knowledge of Morowali Regency. Data collection was carried out through direct observation, interviews and document study. The data collected includes the opinions, views, experiences of informants, as well as numerical data related to the organization and SWOT factors. Data analysis was carried out using the SWOT analysis method which identifies and analyzes the strengths, weaknesses, opportunities and threats faced by Morowali Regency. The results of the SWOT analysis will provide a comprehensive picture of the current situation and become the basis for formulating organizational development strategies that are appropriate to the conditions of Morowali Regency. It is hoped that this research can contribute to strengthening organizational development and improving the performance of Morowali Regency in achieving its strategic goals.